Is Waist-to-Height Ratio a Better Obesity Risk-Factor Indicator for Puerto Rican Children than is BMI or Waist Circumference? - Rivera-Soto, Winna T.; Rodríguez-Figueroa, Linnette (Puerto Rico Health Sciences Journal, 2016)
Objective: Puerto Rican children could have a higher prevalence of obesity, compared to US children or even to US Hispanic children. Obese youths are more likely to have risk factors for cardiovascular conditions, such as hypertension. Although BMI provides a simple, convenient measurement of obesity, it does not measure body fat distribution, associated with mortality and morbidity. Waist circumference (WC) and waist-to-height ratio (WHtR) have been suggested to estimate obesity health risks. This study aimed to explore the association of a single blood pressure reading with 3 different obesity indicators (WC, BMI, and WHtR). Methods: A representative sample of students (first to sixth grade) from public and private schools in Puerto Rico was selected. The sample size consisted of 249 students, representing a 63% response rate. According to the sex-specific BMIs, approximately 38.1% of the children were obese or overweight. The prevalence of obesity was slightly higher when determined using WHtR but lower when using WC as the overweight indicator. The prevalence of high blood pressure among students was 12.5%; an additional 11.3% of the students were classified as possible prehypertensive. Results: Regardless of the weight indicator used, overweight children were shown to have a higher risk of pre-hypertension/hypertension (as defined by a single BP measure) than were non-overweight children. The odds for high blood pressure were almost 3 times higher using WHtR. Logistic regression showed a stronger relationship between WHtR and the risk of pre-hypertension/hypertension than that between the former and either BMI or WC. Conclusion: This study suggests the possibility of higher prevalence of high blood pressure in obese Puerto Rican children. The waist-to height ratio could be the best indicator to measure obesity and potential hypertension in Puerto Rican children.